Cultural anthropology : global forces, local lives - Eller, Jack David
"Cultural Anthropology: Global Forces, Local Lives helps students understand the application of anthropological concepts to the contemporary world. It offers an exceptionally clear and readable introduction to cultural anthropology, closely relating it to key topics such as colonialism and post-colonialism, ethnicity, the environment, cultural change, economic development and globalisation. This second edition includes additional material on medical, urban and political anthropology, as well as increased coverage of religion and culture, with particular focus on Islamic societies. An updated and expanded range of case studies explores the diverse nature of anthropology through appealing subjects as "Blue Jeans Going Global" and "Migrating Brides in Northern India". Students will especially welcome the additional focus on careers in anthropology and how it is used in everyday life"--